Autophagy as a protective mechanism in oxidative stress - N. K. Zenkov; A. V. Chehushkov; P. M. Kozhin; G. G. Martinovich; N. V. Kandalintseva; E. B. Menshchikova (Бюллетень сибирской медицины)
Autophagy is the main catabolic process required for the removal of damaged organelles, aggregated proteins and intracellular pathogens from cells. Oxidative stress is accompanied by an increase in autophagy, which has a protective effect by maintaining the qualitative composition of mitochondria (mitophagy) and peroxisomes (pexophagy) followed by lysosomal degradation of organelles with high production of reactive oxygen species. Aggrephagy also removes toxic products formed during oxidative and carbonyl stress. Furthermore, autophagy can activate the antioxidant response element system and increase the expression of antioxidant enzyme genes. The protective role of autophagy can be useful in many pathological processes accompanied by the development of oxidative stress while at the same time it may cause chemoresistance, reducing the effectiveness of anti-tumor therapy.